Marketing information in firm management - Kretter, Anton (Univerzita Pardubice, 1999)
Based on sound marketing information firm can state a marketing objective and accustomed a firm performance to the needs of the market. For firm management an important supporting factor is developing a relevant marketing information system. To create such information system the firm needs to assign the object of a study that determines firm activity in the market. Such kind of object includes, the main topic area of marketing information system: consumer, user, compititor, and producer input supplier and environment.
Keywords: řízení podniku; Marketing; Marketingové řízení; Informační systémy